A critical review of current laboratory methods used to evaluate mosquito repellents - Luker, Hailey A. (Frontiers in Insect Science, 2024)
Pathogens transmitted by mosquitoes threaten human health around the globe. The use of effective mosquito repellents can protect individuals from contracting mosquito-borne diseases. Collecting evidence to confirm and quantify the effectiveness of a mosquito repellent is crucial and requires thorough standardized testing. There are multitudes of methods to test repellents that each have their own strengths and weaknesses. Determining which type of test to conduct can be challenging and the collection of currently used and standardized methods has changed over time. Some of these methods can be powerful to rapidly screen numerous putative repellent treatments. Other methods can test mosquito responses to specific treatments and measure either spatial or contact repellency. A subset of these methods uses live animals or human volunteers to test the repellency of treatments. Assays can greatly vary in their affordability and accessibility for researchers and/or may require additional methods to confirm results.Here I present a critical review that covers some of the most frequently used laboratory assays from the last two decades. I discuss the experimental designs and highlight some of the strengths and weaknesses of each type of method covered.